Genome of 'Charleston Gray', the principal American watermelon cultivar, and genetic characterization of 1, 365 accessions in the U.S. National Plant Germplasm System watermelon collection. Issue 12 (7th May 2019) - Wu, Shan; Wang, Xin; Reddy, Umesh; Sun, Honghe; Bao, Kan; Gao, Lei; Mao, Linyong; Patel, Takshay; Ortiz, Carlos; Abburi, Venkata L.; Nimmakayala, Padma; Branham, Sandra; et al.
Summary: Years of selection for desirable fruit quality traits in dessert watermelon ( Citrullus lanatus ) has resulted in a narrow genetic base in modern cultivars. Development of novel genomic and genetic resources offers great potential to expand genetic diversity and improve important traits in watermelon. Here, we report a high‐quality genome sequence of watermelon cultivar 'Charleston Gray', a principal American dessert watermelon, to complement the existing reference genome from '97103', an East Asian cultivar. Comparative analyses between genomes of 'Charleston Gray' and '97103' revealed genomic variants that may underlie phenotypic differences between the two cultivars. We then genotyped 1365 watermelon plant introduction (PI) lines maintained at the U.S. National Plant Germplasm System using genotyping‐by‐sequencing (GBS). These PI lines were collected throughout the world and belong to three Citrullus species, C. lanatus, C. mucosospermus and C. amarus . Approximately 25 000 high‐quality single nucleotide polymorphisms (SNPs) were derived from the GBS data using the 'Charleston Gray' genome as the reference. Population genomic analyses using these SNPs discovered a close relationship between C. lanatus and C .  mucosospermus and identified four major groups in these two species correlated to their geographic locations. Citrullus amarus was found to have a distinct genetic makeup compared to C. lanatus and C .  mucosospermus . The SNPs also enabled identification of genomic regions associated with important fruit quality and disease resistance traits through genome‐wide association studies. The high‐quality 'Charleston Gray' genome and the genotyping data of this large collection of watermelon accessions provide valuable resources for facilitating watermelon research, breeding and improvement.